Peningkatan Hasil Belajar Matematika Melalui Kolaborasi Model Pembelajaran Berbasis Masalah dan Pemanfaatan Kelas Maya - Jurnaidi, Jurnaidi (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2019)
This study aims to improve students' mathematics learning outcomes in the material system of two-variable linear equations through the collaboration of Problem Based Learning models and the use of virtual classes in class XI IPA.7, SMA Negeri 8 Palembang. The study was conducted in the 2018/2019 school year with heterogeneous abilities totaling 32 students consisting of 24 women and 8 men. This research method uses quantitative data analysis that compares learning outcomes in the first cycle and the second cycle. Observations are carried out using observation sheets to observe the activities of students during learning. The research took place in two cycles. It can be concluded that the collaboration of problem-based learning models and the use of virtual classrooms can improve student learning outcomes in mathematics. This can be seen from the increase in the number of students who experience mastery learning which is 68.75% in the first cycle, to be 87.50% in the second cycle for the assessment of knowledge, while for the assessment of skills there is also an increase in the number of learners who have mastery learning that is 75, 00% in the first cycle, to 93.75% in the second cycle. Besides the activities of students during learning also increased from 8.66 to 8.84 with the same criteria that is very high.